Assessment of The Effect of Free Cash Flow and Leverage on Earnings Management Practices in Sub-Saharan Africa - Shittu, Saheed Akande; Erasmus, Lourens J. (International Journal of Economics and Financial Issues, 2026)
Earnings Management Practices (EMP) have significant social and economic impact influencing a firm’s business activities and decision-making. Existing studies on EMP in sub-Saharan Africa were mainly based on a few countries and focused almost exclusively on accrual EMP. In contrast, this study examines the effect of Free Cash Flow (FCF) and leverage on both accrual and real EMP among selected listed firms in sub-Saharan Africa. Utilising Larcker and Richardson's model for accrual EMP and Roychowdhury's model for real EMP. The research employs threshold management theory, while the Generalized Method of Moments (GMM) estimator was used to analyse data from 276 non-financial listed firms across six countries for eleven (11) years (2013-2023). The results show that FCF positively and significantly affects accrual EMP but negatively and significantly impacts real EMPs. Unlike leverage that reveal positive and significant effect on accruals and real EMP. The results are of essence to corporate managers and regulators and it is of interest that more disclosure practices and governance should be enhanced to enable investors to navigate the risks of earnings management better so as to make informed decisions.